Síntese e caracterização de pós-cerâmicos do sistema Ca1-xSrxCu3Ti4O12 - Saska Junior, Luiz Antonio [UNESP] (2017)
Ceramics made of CaCu3Ti4O12 (CCTO) create great scientific interest after the discovery of its giant dielectric constant (κ), the high non-ohmic property and photolumenescence. In this study were prepared polycrystalline ceramics in the form of powder with the following composition: Ca1-xSrxCu3Ti4O12 (0.0 ≤ x ≤ 1.0), in which Ca2+ (site A) was gradually replaced by a cation Sr2+. The effects of this graduated replacement were analyzed in the structural and microstructure properties of polycrystalline powders. By the thermogravimetric analysis of the powders, produced by solid state reaction, determined the calcination temperature at 1223K. Analyzing the phases present in the material by the diffraction technique of X-rays its observed that the crystal structure formed is perovskite. When conducting semi-quantitative studies, by the scanning electron microscope with energy dispersive spectroscopy, it was obtained the morphology and chemical composition of the ceramics powders. By the techniques of spectroscopy (infrared, ultraviolet-visible absorption and photoluminescence) were obtained the values 548 cm-1, 500 cm-1 and 415 cm-1, for the vibrational modules of the bonding O-Ti-O, the band gap of 2,85 eV for the studied samples and the optical properties of the powder polycrystalline ceramics were determined.